The Letter Grading System: A Perception and Practice at Secondary Level - Singh, Dhruba Bahadur (NPRC Journal of Multidisciplinary Research, 2025)
This study looks at the perspectives and obstacles of implementing the Letter Grading System (LGS) in the Secondary instruction Examination (SEE), with an emphasis on mathematics instruction in Birendranagar, Surkhet. It discovers that, while teachers and students largely support LGS, substantial misunderstandings exist among stakeholders, resulting in uncertainty, frustration, and resistance. The findings highlight the critical need for planned training and awareness campaigns to clarify the Grade Point Average (GPA) system. Notably, the LGS tends to minimize student dropout rates while expanding prospects for academic success. These findings support recommendations for pedagogical and policy changes to better match assessment techniques with classroom reality. The implications of this research are manifold: it calls for reforms in school evaluation mechanisms and suggests that with adequate pedagogical support, the LGS can enhance classroom practices in mathematics. The study underscores the potential of LGS to act as a catalyst for educational transformation and encourages further research to deepen understanding and refine strategies for effective implementation in diverse educational contexts.